KINERJA SOSIAL DAN KINERJA KEUANGAN YANG DIUKUR MENGGUNAKAN ROA - Elisabeth Kartika Y.W; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
The purpose of this study was to know whether there was reciprocal relationship about corporate social performance and corporate financial performance. Corporate social performance in this study was measured by the Sustainability Reporting Index based on the criteria of GRI version 3.1. Coporate financial performance in this study was measured by Return on Asset (ROA). This study also used firm size and leverage as control variabels. This study used sample of 30 companies listed in IDX and at least had one published sustainability report during the period of 2008-2014. The result of this study found that threre was not reciprocal relationship between corporate social performance and corporate financial performance. But firm size and leverage have negative relationship to corporate social performance and corporate financial performance.